The role of the trans double bond in skin barrier sphingolipids: permeability and infrared spectroscopic study of model ceramide and dihydroceramide membranes - Skolová, Barbora; Jandovská, Kateřina; Pullmannová, Petra; Tesař, Ondřej; Roh, Jaroslav; Hrabálek, Alexandr; Vávrová, Kateřina (Langmuir, 2014)
Dihydroceramides (dCer) are members of the sphingolipid family that lack the C4 trans double bond in their sphingoid backbone. In addition to being precursors of ceramides (Cer) and phytoceramides, dCer have also been found in the extracellular lipid membranes of the epidermal barrier, the stratum corneum. However, their role in barrier homeostasis is not known. We studied how the lack of the trans double bond in dCer compared to Cer influences the permeability, lipid chain order, and packing of multilamellar membranes composed of the major skin barrier lipids: (d)Cer, fatty acids, cholesterol, and cholesteryl sulfate. The permeability of the membranes with long-chain dCer was measured using various markers and was either comparable to or only slightly greater than (by up to 35%, not significant) that of the Cer membranes. The dCer were less sensitive to acyl chain shortening than Cer (the short dCer membranes were up to 6-fold less permeable that the corresponding short Cer membranes). Infrared spectroscopy showed that long dCer mixed less with fatty acids but formed more thermally stable ordered domains than Cer. The key parameter explaining the differences in permeability in the short dCer and Cer was the proportion of the orthorhombic phase. Our results suggest that the presence of the trans double bond in Cer is not crucial for the permeability of skin lipid membranes and that dCer may be underappreciated members of the stratum corneum lipid barrier that increase its heterogeneity.
Keywords: Cholesterol Esters; membrány umělé; Animals; lidé; Membranes, Artificial; Permeability; Sphingolipids; permeabilita; Ceramides; estery cholesterolu; spektrofotometrie infračervená; sfingolipidy; Humans; kůže; Spectrophotometry, Infrared; Skin; ceramidy; zvířata